ANALISIS PERENCANAAN DAN PENGENDALIAN PERSEDIAAN BARANG DAGANG PADA PT. ELECTRONIC CITY INDONESIA, TBK CABANG PALEMBANG - . Sahila (Jurnal RATRI (Riset Akuntansi Tridinanti), 2020)
ABSTRACK The purpose of this study is to determine the planning and control of merchandise inventory which is one of the important aspects in a company to assess whether the inventory of merchandise in the company has been used effectively in the company's operational activities, so seeing the above conditions planning is necessary. and inventory control that has an impact on the effectiveness of inventory management. The analysis used in this research is qualitative and quantitative analysis. Qualitative analysis is used to view the planning and control of the company's merchandise inventory, while quantitative analysis is used to calculate EOQ and Reorder Point as an inventory control tool. The analysis technique that will be used in this research is by using the results of interviews and documentation regarding the planning and control of merchandise inventory at PT. Electronic City Indonesia, Tbk Palembang Branch. The results obtained are that PT. Electronic City Indonesia, Tbk Palembang Branch does not have a good inventory planning and control, as a result there is a shortage and an excess of product inventory. This can affect the company's goals, one of which is to obtain optimal profit.Keywords: Inventory Planning and Control